Revisiting the Global Overfat Pandemic - Maffetone, Philip B.; Laursen, Paul B. (Frontiers in Public Health, 2020)
The previously described overfat pandemic, estimated to be 62–76% worldwide, is comprised of individuals with excess body fat sufficient to impair health. The overfat condition is common in those who are overweight and obese, and can also occur in significant numbers of normal-weight non-obese individuals. Being overfat increases the risk for a wide spectrum of common cardiovascular and metabolic (cardiometabolic) abnormalities, chronic diseases and physical impairment. In some ethnicities, up to 40% or more of those who are normal-weight and non-obese may be overfat, a figure twice that used in the original global overfat estimates. In addition to the rates of overfat outpacing overweight and obesity, non-White populations outnumber Whites 6:1, with the recently estimated overfat prevalence being low when considering ethnicities such as Asians, Chinese, Africans and Latin Americans, including these individuals living among predominantly White populations. An awareness of the extent of the overfat pandemic is important because excess body fat can precede cardiometabolic risk factors, chronic diseases, and physical disabilities, and can reduce quality of life and increase healthcare expenditure. The purpose of this Perspective is to demonstrate that the global overfat prevalence of 62–76% may be considerably underestimated.